Throughput analysis for the mobility of a consumer and an anchorless producer in NDN - Ahmed, muhammed Zaharadeen; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Alkali, Abdulqadir Hamidu; Mohamad, Sarah Yasmin; Morshidi, Malik Arman (Institute of Advanced Scientific Research, 2019)
Named Data networking is a novel communication model that is designed mainly to ensure efficient data dissemination on the internet. In this paper, a practical structure of naming data content in NDN is presented using name based routing as well as mobility first. Simulations are conducted to determine to mobility of both the consumer and producer using NetSim Version 10.1. In the scenario, a mobile consumer is considered to request an audio content from a mobile producer on a single localized NDN network. Afterward, the producer changes its local network to another access network while offering same audio application content to its consumers in the previous localized network and to the new point of attachment. In the results, we compared the voice application throughput and the link throughput and realized that efficiency is achieved using the application throughput as compared to the link. SUMO simulator was used to create the suitable road path for the vehicles before interfacing with NetSim. In addition, the coding system is build using visual studio 2015 and made compatible with NetSim “binary” and “dll” folders. Keywords--- Named Data Networking, consumer, producer, NetSim, Simulation of Urban Mobility, throughput.